2009
DOI: 10.1097/mlr.0b013e31817e189d
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Climate in 92 US Hospitals

Abstract: Differences among and within hospitals suggest that strategies for improving safety climate and patient safety should be tailored for work areas and disciplines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(76 citation statements)
references
References 36 publications
7
62
1
1
Order By: Relevance
“…Importantly, the survey findings show significant differences between the hospital departments in almost all safety culture dimensions and independent items (Appendix 5 and Appendix 6), as also found in other similar studies 1,18,19,41. The findings confirm that culture is created locally,3,40 and thus, efforts to improve safety culture are most likely to have impact if implemented on a departmental, rather than organizational, level 36,41,47.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Importantly, the survey findings show significant differences between the hospital departments in almost all safety culture dimensions and independent items (Appendix 5 and Appendix 6), as also found in other similar studies 1,18,19,41. The findings confirm that culture is created locally,3,40 and thus, efforts to improve safety culture are most likely to have impact if implemented on a departmental, rather than organizational, level 36,41,47.…”
Section: Discussionsupporting
confidence: 84%
“…The findings can be used as a basis to tailor, adopt, and develop interventions that are likely to make an impact in the respective areas. Importantly, safety culture assessment is crucial because different cultural underlying issues of health care workers in different countries, organizations, and units18,19 are strong determinants of successful implementation of an intervention. As an example, a study found that health care workers of public hospitals in China were mostly concerned with blame and shame if and when they make an error during care delivery, which was the opposite to the findings in the USA where fear of shame was the least problematic concern of health care workers 14.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that safety culture perceptions vary across hospitals, units, and disciplines. 2123 Although we did not compare results on the basis of clinical training site, we did find perceived differences in safety culture on IM and surgery clerkships. These differences are not surprising given that students also reported that the “team of providers” and “clinical service” are the most influential to their providing safe care.…”
Section: Discussionmentioning
confidence: 87%
“…Notably, leaders are often associated with having more positive perceptions of the safety culture than frontline workers, and managers and physicians generally reported higher levels of positive perceptions of safety as compared to staff nurses [27]. Singer et al [28] found that among nurses, work experience and work position were significantly associated with perceptions of the patient safety culture. There were more positive reports from nurses who worked on a unit or hospital for more than 10 years, while Kim et al [10] also found distinctions in perceptions of patient safety culture between staff nurses and managers among healthcare workers, but we would propose that this does not go far enough to examine potential differences between staff nurses and charge nurses.…”
Section: Introductionmentioning
confidence: 99%